Improving the odds of survival: transgenerational effects of infections - Victoria M Spanou; Theano P Andriopoulou; Evangelos J Giamarellos-Bourboulis; Mihai G Netea (EMBO Molecular Medicine)
Abstract Recent studies argue for a novel concept of the role of chromatin as a carrier of epigenetic memory through cellular and organismal generations, defining and coordinating gene activity states and physiological functions. Environmental insults, such as exposures to unhealthy diets, smoking, toxic compounds, and infections, can epigenetically reprogram germ-line cells and influence offspring phenotypes. This review focuses on intergenerational and transgenerational epigenetic inheritance in different plants, animal species and humans, presenting the up-to-date evidence and arguments for such effects in light of Darwinian and Lamarckian evolutionary theories. An overview of the epigenetic changes induced by infection or other immune challenges is presented, and how these changes, known as epimutations, contribute to shaping offspring phenotypes. The mechanisms that mediate the transmission of epigenetic alterations via the germline are also discussed. Understanding the relationship between environmental fluctuations, epigenetic changes, resistance, and susceptibility to diseases is critical for unraveling disease etiology and adaptive evolution.